Estudo da via Wnt no endométrio normal e no câncer de endométrio, em mulheres após a menopausa - Menezes, Marina de Pádua Nogueira [UNIFESP] (2011)
The Wnt family is involved in tumorigenesis of several tissues as well in embriogenesis. In order to analize the canonical and noncanonical Wnt pathway in atrophic endometrium and endometrial adenocarcinoma, we evaluated the immunohistochemical expression of Wnt1, Frizzled-1 (FZD1), Wnt5a, Frizzled-5 (FZD5) and ƒÀ-catenin. Endometrial specimens were obtained from surgeries performed between 1995 and 2005 and the patients were divided in two groups: Group A, atrophic endometrium (N = 15); Group B, endometrial adenocarcinoma (N = 45). Immunoreactivity for Wnt1, FZD1, Wnt5a, FZD5 and ƒÀ-catenin was scored for each group. For the expression of Wnt1, FZD1 and Wnt5a, no significant association was observed between the groups. A significant association was observed between the groups for the FZD5 expression (p = 0.001). The proportion of FZD5 positive women was significantly higher for group A (80.0%) compared to group B (31.1%). Regarding the survival curve for FZD5 at group B, we found no significant association between positive and negative women. No significant association was observed between s-catenin expression and the patient group since the expression for groups A and B were 100% and 95.6%, respectively (p = 1.000). FZD5 is downregulated in type I endometrial adenocarcinoma when compared to atrophic endometrium.